Patients with Achilles tendon injuries – how are function and quality of life affected? - Albuquerque, Bruno Mota; Borges, Vinícius Quadros; Ferraz, Gabriel Ferreira; Stéfani, Kelly Cristina (Scientific Journal of the Foot & Ankle, 2018)
Objective: To evaluate the late postoperative results for quality of life after surgical treatment of Achilles tendon rupture by open surgery and peroneus brevis tendon transfer. Methods: This prospective cohort study included patients who underwent surgical treatment for Achilles tendon rupture by open surgery and peroneus brevis tendon transfer and evaluated these patients in outpatient follow-up. Functional and quality-of-life scores were determined in the late postoperative period. Results: The sample consisted of 32 patients with spontaneous tendon rupture primarily caused by practising recreational sports (81.1%). The mean age was 44.6 years, and the mean body mass index was 28.1Kg/m2; most of the patients were men. The rate of complications related to suture dehiscence in the immediate postoperative period was 31%. The World Health Organization Quality of Life-Abbreviated (WHOQOL-BREF) score was 15.2±2.45, the Foot Function Index Revised (FFI-R) score was 42.59±0.16, the Short Musculoskeletal Function Assessment (SMFA) score was 15.60±16.74, and the American Orthopaedic Foot and Ankle Society (AOFAS) hindfoot score was 80.16±15.08. Conclusion: The late postoperative functional results of open surgical treatment of tendon rupture were satisfactory using the AOFAS score and unsatisfactory using the FFI-R score. The quality-of-life outcomes were satisfactory using the WHOQOL-BREF score and unsatisfactory using the SFMA score. Both the FFI-R and SFMA scores indicated that the main patient complaints were stiffness of the affected limb and pain/ discomfort in the tendon that was surgically treated. Level of Evidence II; Prospective Cohort Study.